EFFECT OF IRON AND SELENIUM DRUGS ON DIASTOLIC MYOCARDIAL FUNCTION IN PATIENTS WITH ANEMIC CARDIOMYOPATHY - E. V. Goncharova; A. V. Govorin (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study the changes of the left (LV) and right (RV) ventricles diastolic function, the segmental LV diastolic function in patients with anemic cardiomyopathy after the iron and selenium drugs therapy.Material and methods. Patients (n=54) with severe chronic post-hemorrhagic iron deficiency anemia, complicated by cardiomyopathy were treated with iron sulfate and sele- nium. Segmental LV diastolic function was evaluated with pulsed tissue Doppler, and global diastolic function of the LV and RV – with Doppler echocardiography, before and af- ter treatment. Control group contained 16 healthy individualsResults. Disorders of segmental LV diastolic function, and both ventricles global diastolic function were found in anemic patients with cardiomyopathy. Flow rate rapid filling re- duced by 27.1% compared with this in control (p<0.001), and flow rate of atrial filling increased by 27.0% (p<0.001), and E/A decreased by 42.2% (p<0.001). Iron and se- lenium therapy in patients with anemic cardiomyopathy led to an improvement in diastolic function. LV and RV flow rapid filling increased by 32.2% (p<0.001) and 8.3% (p<0.05), respectively, and LV and RV flow rate of atrial filling reduced by 19.6% and 15.7% (p<0.001), respectively, and LV and RV E/A ratio grew up by 61.5% and 28.2%, respective- ly (p<0.001).Conclusion. Echocardiography and myocardial tissue Doppler provide early finding of segmental LV diastolic function disorders in anemic cardiomyopathy. Iron and selenium ther- apy leads to improvement of myocardial diastolic function in these patients.